Analysis of Social Media Digital Marketing Strategies for GNC Regency 2 Housing at PT Gita Nugraha Cipta Palembang - ilham sakti; Rahmanda Akilla (International Journal of Advanced Research in Social Studies, 2025)
This final research report aims to examine the digital marketing strategies implemented through Instagram by PT Gita Nugraha Cipta Palembang in promoting the GNC Regency 2 housing project. The study adopts a descriptive qualitative approach, with data collected through interviews, documentation, and a review of relevant literature. The findings indicate that the company’s digital marketing strategy has not yet been fully optimized, particularly in terms of social media engagement, content utilization, and the competencies of the digital marketing team. A SWOT analysis reveals that the company’s strengths lie in its strategic location and competitive pricing, while its primary weakness is the suboptimal management of social media platforms. Accordingly, the study recommends several strategic improvements, including enhancing the quality and consistency of digital content, strengthening the capabilities of the digital marketing team, and maximizing the use of social media features to foster closer relationships with potential consumers.